Zone of tolerance for healthcare services: a diagnostic model of public and private hospital service quality - Nadiri, Halil; Hussain, Kashif (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2016)
This study compares the quality of services provided by public and private hospitals in North Cyprus. The paper describes the zone of tolerance for patients’ service expectations and determines patient satisfaction level for public and private hospitals. The ‘zone of tolerance’ is recognized in the service-quality literature as representing a range of expectations (desired and adequate) and an area of acceptable outcomes in service interactions. The patient satisfaction level of public and private hospitals is identified and compared. The conceptual model, HEALTHZOT, is presented in this study and the results demonstrate that the evaluation of services can be scaled according to different types of expectations – ‘desired’ and ‘adequate’ – and that patients use these two types of expectations as a comparison standard in evaluating healthcare services. The results obtained for public and private hospital services represent a narrow zone of tolerance. Patients’ ‘perceived service received’ in public hospitals was lower when compared to private hospital services. The results of an exploratory factor analysis reveal that the SERVQUAL model is found to be unidimensional for both the public and private hospitals in this study. The results, managerial implications and future research implications are discussed below in detail
Argumenta Oeconomica, 2016, Nr 2 (37), s. 245-280
Keywords: service quality; customer satisfaction; zone of tolerance; healthcare services; public and private hospitals